FRI0388 Us lung examination in ssc patients: could we simplify it?. (23rd January 2014) - Delle Sedie, A.; Pepe, P.; Lodato, C.; Cioffi, E.; Carli, L.; Bombardieri, S.; Riente, L.
Abstract : Background: Systemic sclerosis (SSc) is a disease characterized by a progressive fibrosis of the skin and internal organs, which can lead to death. Lung involvement includes a wide range of disorders and interstitial lung disease (ILD) is the most common manifestation, being clinically significant in about 40% of patient. Recently, the role of US in the assessment of ILD (counting the B-lines, generated by the reflection of the US beam from thickened sub-pleural interlobar septa) has been confirmed after comparison with high-resolution computed tomography (HRCT) and a few scoring systems proposed. The comprehensive examination of lung intercostal spaces (LIS) is time consuming (54 LIS in each patient) and a previous attempt to give a simplified US B-line scoring system has been done in connective tissue diseases patient (1). Objectives: To investigate which LIS are more frequently involved in SSc patients, with and without ILD, in order to find a reduced number of LIS to scan using US. Methods: Seventy-nine SSc patients were enrolled independently of the presence of any dispnoea. Each patient underwent a lung US with comprehensive US B-line assessments by an experienced rheumatologist. A cut-off of >12 B-lines was decided based on the correlation between US and HRCT in 76 patients, then US was performed alone in the rest of the SSc patients. The presence/absence of B-lines was registered in each LIS. Results: A highly significant correlation between US assessment and HRCT was found (ICC=0.576; sensitivity and specificity were 81 and 73%, respectively). Single LIS significantly correlates to the diagnosis of ILD + in 41/54. In a multivariate analysis, even examining only 2 LIS, sensitivity and specificity of the US, with respect to the comprehensive scan, remains high (93.5 and 81.4%, respectively). Conclusions: Most of single LIS significantly correlate to the presence of ILD. Even scanning only the 5 th right emiclavear and the 3 rd left parasternal LIS, sensitivity and specificity of US examination remains high. References: Gutierrez M, Salaffi F, Carotti M et al. Arthritis Res Ther 2011;13(4):R134. Disclosure of Interest : None Declared